Peran Kelompok Keagamanaan dalam Menjaga Keharmonisan dan Keberagaman - Muhammad Fajar Awwaludin; Rachmat Ramdani (Peneliti.net, 2022)
Diversity is a necessity for the Indonesian people, the diversity of the Indonesian people is natural and has been a source of wealth for the Indonesian nation since the nation's ancestors. As a multicultural and multi-religious nation, Indonesia is known as a country full of tolerance. The lives of citizens in society, nation and state have a harmonious relationship. From previous studies, it is known that the recipe for harmony is the plurality of people who have walked the trail, and the existence of local wisdom and interfaith forums, such as the Religious Harmony Forum (FKUB). This study deepens the role of religious groups that support the conditions of social harmony. This is intended to determine the role of religious groups in maintaining social harmony and diversity in the Karawang and Sukabumi districts. By reviewing literature, interviews, and field observations, this study identifies the role of religious groups, namely the Nahdhatul Ulama (PCNU) Branch Manager in Karawang Regency and the Vihara Nam Hai Kwan Se Im Pu Sa in Sukabumi Regency by holding meetings in open forums and collaborating in activities everyday life among people can effectively manage various problems and maintain harmony.